Determine the Relationship Between Locus of Control with Learning Outcomes in Reproductive Health Subject in the Second Semester Students of Midwifery Program Study (D. III) of Kadiri University - Prasetyanti, Dhita Kris (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Learning outcome is the ability of students in doing tasks assigned by lecturers, appearance or behavior in executing its task, attitudes, methods used in doing the task. The factors that most influence the outcome of learning is Locus Of Control factor. Internal Locus of Control is the extent to which a person expects that a strengthening or the results of their behavior depends on their own behavior or personal characteristics. The purpose of this study was to determine the relationship between locus of control with learning outcomes in reproductive health subject in the second semester students of Midwifery Study Program (D. III) of FIK University of Kadiri.Research’s design used was correlational analtic research. The population of this research were all of the Midwifery student (D. III) enrolled in the second semester of University of Kediri in total of 53 students with a technique namely total of population obtained 53 sample. Research’s instrument used was questionairre. Research’s results were then analyed by using spearman rank The results of the research carried out showed that most of Locus Of Control students of D III majoring in Midwifery in the second semester of Faculty of Health Sciences University of Kadiri included in Locus Of Control Internal. The results of the analysis showed that there are average relationship and positive direction (+) between Locus of Control and most of the learning outcome of the subject of reproductive health in the students of second semester (D III) Faculty of Health Sciences of University of Kadiri year 2015. Based on the research’s results it is epected to gain more attention for more research to be carried out and study several matters affecting the process of learning-teaching so that it would be more optimal in addition to locus of control factor. Keywords : Locus of Control, Learning Results, Reproduction Health, Students